Dropshipping in a Contemporary Muamalah Fiqh Perspectives - Aina Nur Hilmy Harahap; Doni Doni; Ahmad Rifai; Ali Imran Sinaga (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research aims to analyze the dropshipping model according to Islamic jurisprudence. The research focuses on the completeness of the terms and conditions of buying and selling in the dropshipping system and how they relate to three economic disasters, namely zhulm, usury and ghoror. The novelty of this research is that it divides transaction objects into two categories, ribawi goods and non-ribawi goods and criticizes the arguments that allow dropshipping transactions. Literature studies are used to define dropshipping, normative descriptive models are used to define contracts in dropshipping according to Islam. In jurisprudence, content analysis is used to find syar’i solutions in dropshipping. The results show that the law of origin in dropshipping is prohibited (haram) because it contains usury nasi’ah for ribawi goods and selling before ownership of non-ribawi goods. The syar’i solutions found for dropshipping are modified ijab qobul, wakalah bil ujroh (dropshipper becomes consumer representative) and ba’ salam, but the final solution is marjuuh, because capital is not distributed at the start of the assembly.